Impact of Invasive Bees on Plant-Pollinator Interactions and Reproductive Success of Plant Species in Mixed Nothofagus antarctica Forests - Agüero, Juan I. (2020)
Fil: Agüero, Juan I. Universidad de Buenos Aires. Facultad de Agronomía. Cátedra de Botánica General; Argentina.